MicroRNA-655-3p regulates Echinacea purpurea mediated activation of ABCG2. (3rd October 2018) - Awortwe, Charles; Kaehler, Meike; Rosenkranz, Bernd; Cascorbi, Ingolf; Bruckmueller, Henrike
Abstract: 1. The aim of this study was to investigate the regulatory effect of Echinacea purpurea (EP) on efflux transporters ABCB1 and ABCG2 and to identify specific microRNAs contributing to their post-transcriptional regulation. 2. ABCB1 and ABCG2 levels were assessed in human hepatoblastoma HepG2 cells treated with 50 µg/mL methanolic extract of commercial EP capsules for different durations. The microRNA expression profile of HepG2 cells after EP treatment was evaluated and in silico target prediction was subsequently conducted to identify specific microRNAs with binding sites in the 3′-UTR of ABCB1 and ABCG2. Luciferase reporter gene assays and site-directed mutagenesis were used to confirm the binding site of identified microRNA within the 3′-UTR of the target gene. 3. EP increased ABCB1 (10-fold ± 3.4, p < 0.001) and ABCG2 (2.7-fold ± 0.5, p < 0.01) mRNA levels after 12 h exposure. Twenty-four microRNAs showed significant expression differences at all durations of exposure to EP. MiR-655-3p showed a 6.79-fold decrease in expression after 12 h exposure compared to 0 h, was predicted in silico to bind ABCG2 3′-UTR and showed a significant negative correlation ( p = 0.01) to ABCG2 expression level. The binding of miR-655-3p to ABCG2 3′-UTR was confirmed by reporter gene assays (reduction of reporter gene activity to 60%; p = 0.0001). 4. These results suggest that EP regulates ABCG2 expression via downregulation of miR-655-3p in the liver cells. Thus, miR-655-3p downregulation could be applied to predict EP mediated drug interactions.